The Role of Indigenous Plants in Sustaining Food Sources in Lesten Village, Gayo Lues Regency, Indonesia - Monalisa, Monalisa; Mukramah, Mukramah; Fathiya, Nir; Saudah, Saudah; Rayhannisa, Rayhannisa (Grimsa Journal of Science Engineering and Technology, 2024)
The Gayo tribe in Lesten Village has historically relied on plants to fulfill their nutritional needs. Expanding knowledge about diverse plant-based food sources offers a promising strategy for addressing future food insecurity. A dependence on conventional plant species has often resulted in inadequate food supplies, highlighting the need for alternative approaches that incorporate a broader range of plant resources to mitigate food scarcity. Located within the Leuser mountain buffer landscape, Lesten Village in Gayo Lues Regency, Aceh Province, represents a key agricultural area with significant potential to benefit the local community. This study aimed to document and analyze the plant species used as food sources by the Lesten Village community. Data collection combined qualitative and quantitative methods, including exploration, direct observation, and semi-structured interviews. The results revealed that female respondents had a higher level of knowledge about plant use as food sources. Notably, 52.9% and 55.7% of these respondents were aged 50 years or older. The community in Lesten utilized a total of 51 plant species from 26 families as food ingredients. Vegetables constituted the largest category (34%), followed by spices (30%), fruits (21%), and carbohydrates (15%). Fruits were the most frequently used plant part for food (61%). The species with the highest use value was Cacica papaya (1.07). Additionally, the traditional food with the highest fidelity level was serbet (62.82%). These findings emphasize the importance of integrating a diverse range of plant resources into food systems to enhance food security and stimulate economic development in the region.